Tandem aza-michael-condensation-aldol cyclization reaction: approach to the construction of DE synthon of (+/-)-camptothecin - Chavan, Subhash P.; Dhawane, Abasaheb N.; Kalkote, Uttam R. (Synlett, 2008)
An efficient synthesis of the DE ring of camptothecin, employing a Reformatsky and a tandem one-pot, three-step transformation involving aza-Michael reaction, condensation with ethyl malonyl chloride followed by intramolecular `aldol' reaction to furnish the dihydropyridone derivative from commercially available starting materials, has been achieved.
Keywords: Aldol cyclizations; alkaloids; antitumor; Natural products; Reformatsky reaction